METHOD FOR PRODUCING INJECTION-MOLDED BODY - NAKAMURA NOBUO; SATO SHUNSUKE; KATSUTA YUTA (2022)
Provided is a method for producing an injection-molded body from a molding material including a poly(3-hydroxybutyrate)-based resin, wherein the molding material has a difference of 10-70 DEG C between the melting point peak temperature and the melting point peak end temperature as measured by differential scanning calorific value analysis, the method comprising: a step for heating and melting the molding material at a temperature between the melting point peak temperature and the melting point peak end temperature, and injecting the molding material into a mold having a temperature of 30-80 DEG C; and a step for cooling and solidifying the molding material in the mold into crystals. 本发明提供由包含聚(3-羟基丁酸酯)类树脂的成型材料制造注塑成型体的方法，该方法包括：以使上述成型材料的温度达到上述熔点峰值温度与上述熔点峰的结束温度之间的方式进行加热熔融，并射出至温度为30℃～80℃的范围的模具的工序；以及在该模具内将上述成型材料冷却而使其结晶凝固的工序，上述成型材料在差示扫描量热分析中的熔点峰值温度与熔点峰的结束温度之差为10℃以上且70℃以下。